The sociological imagination and inclusive pedagogy - Knight Johnson, Lenore M. (International journal of Christianity & education, 2026)
The recent growth in online learning coupled with the COVID-19 pandemic has given educators much to think about in terms of how to deliver course content in ways that maintain values of inclusivity, community, and belonging. As sociologists teaching students at a Christian liberal arts college, our research explores how hybrid pedagogy, combining face-to-face and asynchronous, online learning opportunities, impacts students? development of a sociological imagination and contributes to an overall sense of belonging and inclusion in the classroom. After adapting a foundational sociology course due to scheduling and logistical needs, we discovered how this pedagogical change expanded student engagement across lines of difference and broadened their awareness and understanding of how they, as individuals, are connected to others and our wider social landscape. Our intentional reflection on the changes to our class and student development of a sociological imagination allowed us to see how adapted pedagogy aligns with our Christian commitment to inclusivity and belonging. Along with sharing our experience and findings, we offer several reflections for all educators to consider for strengthening diverse student experiences.